2013
DOI: 10.1007/s00792-013-0594-9
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate and halophilic prokaryotes: implications for possible halophilic life on Mars

Abstract: In view of the finding of perchlorate among the salts detected by the Phoenix Lander on Mars, we investigated the relationships of halophilic heterotrophic microorganisms (archaea of the family Halobacteriaceae and the bacterium Halomonas elongata) toward perchlorate. All strains tested grew well in NaCl-based media containing 0.4 M perchlorate, but at the highest perchlorate concentrations, tested cells were swollen or distorted. Some species (Haloferax mediterranei, Haloferax denitrificans, Haloferax gibbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 32 publications
2
92
1
1
Order By: Relevance
“…Perchlorate has been previously reported at somewhat higher levels for two locations on Mars' surface (49-51), but higher concentrations might not prove to be a serious constraint, because Oren et al (32) have reported tolerance of up to 0.4 M sodium perchlorate by several extreme halophiles. Indeed, in addition to tolerating perchlorate, some CO oxidizers might be able to use it as a respiratory electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perchlorate has been previously reported at somewhat higher levels for two locations on Mars' surface (49-51), but higher concentrations might not prove to be a serious constraint, because Oren et al (32) have reported tolerance of up to 0.4 M sodium perchlorate by several extreme halophiles. Indeed, in addition to tolerating perchlorate, some CO oxidizers might be able to use it as a respiratory electron acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in addition to tolerating perchlorate, some CO oxidizers might be able to use it as a respiratory electron acceptor. Perchlorate reduction using organic substrates has been reported for several extremely halophilic euryarchaeotes (32,52), but A. ehrlichii MLHE-1 did not oxidize CO with perchlorate (Fig. S2) ), and an analogous process, perchlorate-dependent hydrogen oxidation, has been used for perchlorate bioremediation (53).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general terms, Haloferax growth under those microaerobic or even strict anaerobic conditions is possible because oxygen is replaced by other final electron acceptors such us nitrate, nitrite (Lledó, Martinez-Espinosa, Marhuenda-Egea & Bonete, 2004;Bonete et al, 2008;Nájera-Fernández, Zafrilla, Bonete & Martinez-Espinosa, 2012;Esclapez, Zafrilla, Martinez-Espinosa & Bonete, 2013) (per)chlorate (Oren, Elevi-Bardavid & Mana, 2014; Martínez-Espinosa, Richardson & Bonete, 2015), sulphur or sulphide (Elshahed et al, 2004), arsenate (Rascovan, Maldonado, Vazquez & Eugenia Farias, 2015), dimethyl sulfoxide (DMSO), trimethylamine N-oxide (TMAO) and fumarate (Oren & Trüper, 1990;Oren, 1991;Oren, 1999;Müller & DasSarma, 2005).…”
Section: Anaerobic Metabolism In the Haloferax Genusmentioning
confidence: 99%
“…The adaptive strategies for tolerance at high MgSO 4 concentrations were not explored, but the authors noticed some unexplained differences in the growth rate and stationary-phase maximum densities when their isolates were exposed to different sulfate salts. There are some reports about the substitution of NaCl with other salts (Oren et al, 2014), but very few in the context of exploring the possibilities of survival of terrestrial microorganisms in an Europan scenario.…”
Section: Introductionmentioning
confidence: 99%